2021
DOI: 10.1016/j.xpro.2021.100804
|View full text |Cite
|
Sign up to set email alerts
|

A time-resolved fluorescence resonance energy transfer screening assay for discovery of protein-protein interaction modulators

Abstract: Summary Protein-protein interactions (PPIs) have emerged as promising yet challenging therapeutic targets. A robust bioassay is required for rapid PPI modulator discovery. Here, we present a time-resolved Förster's (fluorescence) resonance energy transfer assay protocol for PPI modulator screening in a 1536-well plate format. We use hypomorph SMAD4 R361H -SMAD3 PPI as an example to illustrate the application of the protocol for screening of variant-directed PPI inducers. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Simplified representation of overlapping synthetic peptides used to map the different interaction regions in the FSH-β subunit. The peptide FSH-β-(31-45) identified in this study, shown in the red circle, included the region FSH-β-(34)(35)(36)(37), previously identified as a receptor-binding region[174].…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Simplified representation of overlapping synthetic peptides used to map the different interaction regions in the FSH-β subunit. The peptide FSH-β-(31-45) identified in this study, shown in the red circle, included the region FSH-β-(34)(35)(36)(37), previously identified as a receptor-binding region[174].…”
mentioning
confidence: 67%
“…Other in vitro techniques have been developed for determining the binding affinity of PPIs. Methods such as Förster resonance energy transfer (FRET), time-resolved (TR)-FRET [31][32][33][34], protein-fragment complementation assays (PCAs) [35], which require labelling of the interacting components, have been extensively used to study PPIs in a cellular context as well [33,[35][36][37]. However, covalent labeling may alter the structural properties of the molecules interfering with the proper protein recognition.…”
Section: Identification Of Protein Partnerships and Characterization ...mentioning
confidence: 99%
“…Thus, to expedite the discovery of SMAD4 inhibitors through high-throughput screening (HTS), the development of a robust and scalable bioassay capable of simultaneously monitoring the cooperative dynamics of SMAD4–SMAD3–DNA PPI and PDI is highly desirable. With this objective in mind, we investigated the feasibility of a cell lysate-based TR-FRET assay ( Li et al., 2017 ; Tang et al., 2021b ).…”
Section: Resultsmentioning
confidence: 99%
“…With this objective in mind, we investigated the feasibility of a cell lysate-based time-resolved fluorescence resonance energy transfer (TR-FRET) assay. 18,19 TR-FRET is a well-established bioassay widely utilized for monitoring molecular interactions. In essence, TR-FRET signal arises from a proximity-based resonance energy transfer (<10nm) between a long-lived donor fluorophore, such as terbium (Tb), and an acceptor fluorophore with a spectrum that overlaps with the donor.…”
Section: Design Of the Multiplexed Smad4-smad3-dna Tr-fret Assaymentioning
confidence: 99%
“…The SMAD4 and SMAD3 MH2 domain truncation plasmids were generated by PCR using Platinum™ Taq DNA Polymerase kit (Thermo Fisher Scientific) and respectively the SMAD4 or SMAD3 pDONR221 plasmid as DNA template and the Gateway cloning (Invitrogen) was used to generate GST-tagged, Venus-flag-tagged, Flag-tagged and 6XHis-tagged plasmids as previously described. 14,18,19,[32][33][34] The vector backbones are pDEST27 vector (Invitrogen) for GST-tag, pDEST26 (Invitrogen) for 6XHis tag, pSCM167 for Venus-flag-tag, pcDNA3.2-V5-dest for Flag-tag constructs. All plasmids generated were confirmed by sequencing.…”
Section: Molecular Cloning and Mutagenesismentioning
confidence: 99%